2021
DOI: 10.1002/adma.202107420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry Advances High‐Performance Perovskite Solar Cells

Abstract: A prerequisite for commercializing perovskite photovoltaics is to develop a swift and eco‐friendly synthesis route, which guarantees the mass production of halide perovskites in the industry. Herein, a green‐solvent‐assisted mechanochemical strategy is developed for fast synthesizing a stoichiometric δ‐phase formamidinium lead iodide (δ‐FAPbI3) powder, which serves as a high‐purity precursor for perovskite film deposition with low defects. The presynthesized δ‐FAPbI3 precursor possesses high concentration of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 62 publications
0
82
0
Order By: Relevance
“…53 However, in the MAPbI 3 nanowire sample with BMIMBF 4 (Figure S21B), a great quantity of charge carriers (excited to the CB) will transfer from MAPbI 3 to BMIMBF 4 owing to the existence of the charge transfer layer, leaving a small number of electrons return to the VB, thus showing low PL intensity and short TRPL lifetime. 53 Additionally, the improved energy level arrangement of the MAPbI 3 nanowire sample with BMIMBF 4 compared with that of the MAPbI 3 nanowire sample without BMIMBF 4 (Figure S22) further proves that the addition of BMIMBF 4 is conducive to charge transfer in MAPbI 3 nanowires. 54 To further understand how the introduction of BMIMBF 4 realizes the charge carrier transfer effect in MAPbI 3 nanowires, the adsorption of BMIMBF 4 on the MAPbI 3 surface was investigated using DFT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…53 However, in the MAPbI 3 nanowire sample with BMIMBF 4 (Figure S21B), a great quantity of charge carriers (excited to the CB) will transfer from MAPbI 3 to BMIMBF 4 owing to the existence of the charge transfer layer, leaving a small number of electrons return to the VB, thus showing low PL intensity and short TRPL lifetime. 53 Additionally, the improved energy level arrangement of the MAPbI 3 nanowire sample with BMIMBF 4 compared with that of the MAPbI 3 nanowire sample without BMIMBF 4 (Figure S22) further proves that the addition of BMIMBF 4 is conducive to charge transfer in MAPbI 3 nanowires. 54 To further understand how the introduction of BMIMBF 4 realizes the charge carrier transfer effect in MAPbI 3 nanowires, the adsorption of BMIMBF 4 on the MAPbI 3 surface was investigated using DFT.…”
Section: Resultsmentioning
confidence: 99%
“…We think that the introduction of BMIMBF 4 forms a charge transfer layer on the surface of MAPbI 3 nanowire film, which provides a transport channel for the photogenerated carriers 52 . As illustrated in Figure S21, for the MAPbI 3 nanowire sample without BMIMBF 4 (Figure S21), since there is no charge transfer layer on the surface of MAPbI 3 nanowire film, after the system reaches equilibrium, a large number of charge carriers excited to the conduction band (CB) return to the valence band (VB) and perform radiation‐composite luminescence with the holes in the VB, thus appearing strong PL intensity and long TRPL lifetime 53 . However, in the MAPbI 3 nanowire sample with BMIMBF 4 (Figure S21B), a great quantity of charge carriers (excited to the CB) will transfer from MAPbI 3 to BMIMBF 4 owing to the existence of the charge transfer layer, leaving a small number of electrons return to the VB, thus showing low PL intensity and short TRPL lifetime 53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both perovskite precursor solutions exhibited the light-scattering behaviour typical of colloidal dispersions. [25] The colloid sizes of both perovskite precursor solutions were mainly distributed in the 10-100 nm range, with a larger average colloid size for the PSPP perovskite precursor solution in this range. In addition, the PSPP precursor solution contained large-size colloids in the 5000-10 000 nm range.…”
Section: Methodsmentioning
confidence: 92%
“…Moreover, the δ-FAPbI 3 powder shows outstanding storage stability for more than 10 months in ambient with 40 ± 10% RH. 60 Wang et al reported a novel technique of isothermally depositing highlyoriented perovskite film at room temperature (RT). They discovered that amine-assisted crystallographic lattice expansion can transform initial 3D perovskite into metastable low-dimensional intermediate.…”
Section: Raw Materialsmentioning
confidence: 99%